Synthetic cannabinoid JWH-073 alters both acute behavior and in vivo/vitro electrophysiological responses in mice - Barbieri, Mario; Tirri, Micaela; Bilel, Sabrine; Arfè, Raffaella; Corli, Giorgia; Marchetti, Beatrice; Caruso, Lorenzo; Soukupova, Marie; Cristofori, Virginia; Serpelloni, Giovanni; Marti, Matteo (Frontiers in Psychiatry, 2022)
JWH-073 is a synthetic cannabinoid (SCB) that is illegally marketed within an “herbal blend”, causing psychoactive effects more intense than those produced by Cannabis. Users report that JWH-073 causes less harmful effects than other SCBs, misrepresenting it as a “safe JWH-018 alternative”, which in turn prompts its recreational use. The present study is aimed to investigate the in vivo pharmacological activity on physiological and neurobehavioral parameters in male CD-1 mice after acute 1 mg/kg JWH-073 administration. To this aim we investigate its effect on sensorimotor (visual, acoustic, and tactile), motor (spontaneous motor activity and catalepsy), and memory functions (novel object recognition; NOR) in mice coupling behavioral and EEG data. Moreover, to clarify how memory function is affected by JWH-073, we performed in vitro electrophysiological studies in hippocampal preparations using a Long-Term Potentiation (LTP) stimulation paradigm. We demonstrated that acute administration of JWH-073 transiently decreased motor activity for up to 25 min and visual sensorimotor responses for up to 105 min, with the highest effects at 25 min ( 48 and 38%, respectively), while the memory function was altered up to 24 h ( 33%) in treated-mice as compared to the vehicle. EEG in the somatosensory cortex showed a maximal decrease of α ( 23%) and γ ( 26%) bands at 15 min, β ( 26%) band at 25 min, a maximal increase of θ ( 14%) band at 25 min and δ ( 35%) band at 2 h, and a significant decrease of θ ( 18%), α ( 26%), and β ( 10%) bands during 24 h. On the other hand, EEG in the hippocampus showed a significant decrease of all bands from 10 min to 2 h, with the maximal effect at 30 min for θ ( 34%) and γ ( 26%) bands and 2 h for α ( 36%), β ( 29%), and δ ( 15%) bands. Notably, the δ band significant increase both at 5 min ( 12%) and 24 h ( 19%). Moreover, in vitro results support cognitive function impairment ( 60% of decrease) by interfering with hippocampal synaptic transmission and LTP generation. Our results suggest that JWH-073 deeply alters brain electrical responsiveness with minor behavioral symptoms. Thus, it poses a subtle threat to consumers who mistakenly consider it safer than other SCBs.